Improvement of student’s creative thinking skills by guided inquiry-based student worksheet in acid-base materials - Nofi Eriana Sulistiani; Rudiana Agustini (Jurnal Pendidikan Kimia (JPKIM), 2022)
This study aims to create students’ worksheets based on guided inquiry which are valid, practical and effective to gain students' skill in creative thinking in acid-base materials. This study was a Research & Development (R&D) using the 4-D method (Define, Design, Develop, Disseminate). The subjects implemented to this research were 29 students of class XI MIA MAN 4 Kediri. A design of one-group pretest-posttest without any comparison was used to conduct this research. Regarding the outcomes of the research, this can be summed up that 1). The validity of guided inquiry-based students’ worksheet obtained score of 89.60% with very valid criteria on content validation and 85.23% with very valid criteria in construct validation. 2). The practicality of guided inquiry-based students’ worksheet obtained values in the range of 70.96%-96.77% and on practical and very practical criteria. 3). The effectiveness of guided inquiry-based students’ worksheet obtained an increase in N-gain in four indicators of creative thinking skills of more than 0.7 with high criteria. It can be concluded that the students that used guided inquiry based worksheet enhanced student’s academic achievment in acid base materials.Keywords: Acid-base; Creative thinking skill; Guided inquiry; Student worksheet